2018
DOI: 10.1021/acs.langmuir.8b00322
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Vascular Distribution and Adhesion of Nanoparticles with Protein Corona in Microflow

Abstract: The protein corona has emerged as an important determinant of biological response in nanoparticle (NP) drug delivery. However, there is presently no reported study on how the protein corona affects the behavior of NPs in microflow and its subsequent interactions with the vascular endothelium, which could affect their delivery to the target tumor site regardless of its targeting mechanism. Furthermore, a consensus on the role of physical and surface characteristics of NPs in affecting the margination of NPs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…migration towards the wall) of nanoparticles under flow conditions via the formation of protein corona, leukocyte-assisted trafficking as well as through alteration of the ratio between inertial and Brownian forces. 8,40,44,46,47 Furthermore, PHY (being a fusogenic lipid) may undergo competitive interactions between the blood and tissue cells. Numerous previous studies have shown that PHY-based nanoparticles are capable of exerting extensive hemolytic action at 10-times lower concentrations than that causing tissue cytotoxicity, even in the presence of Poloxamers (ranging between 3-30 % w/w).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…migration towards the wall) of nanoparticles under flow conditions via the formation of protein corona, leukocyte-assisted trafficking as well as through alteration of the ratio between inertial and Brownian forces. 8,40,44,46,47 Furthermore, PHY (being a fusogenic lipid) may undergo competitive interactions between the blood and tissue cells. Numerous previous studies have shown that PHY-based nanoparticles are capable of exerting extensive hemolytic action at 10-times lower concentrations than that causing tissue cytotoxicity, even in the presence of Poloxamers (ranging between 3-30 % w/w).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Its hydrophilic and lipophilic properties, combined with its capacity for self‐organizing micelles, render it suitable for drug delivery 338 . Additionally, it finds extensive application in piggyback cells, 339 proteins, 340 growth factors, 341 and so on. Poloxamer 188, poloxamer 127, poloxamer 237, and poloxamer 407 are frequently used in biomedical engineering 334,342–345 .…”
Section: The Future Of Regenerative Medicine In Cyclical Endometrial ...mentioning
confidence: 99%
“…In recent years, computational methods or simulated tools to obtain detailed view of nanocarriers-organs interactions during their transport to tumors have become increasingly popular. Kiew et al (2017) and Ho et al (2018) investigated the permeability of nanocarriers in vitro using biomimetic microfluidic models. These techniques enabled preliminary assessment on the delivery efficiency of nanocarriers, which can provide a feedback system to formulation studies.…”
Section: Opportunitiesmentioning
confidence: 99%